Nag Hammadi Codices III, 3-4 and V,1 with Papyrus Berolinensis 8502,3 and Oxyrhynchus Papyrus 1081: Eugnostos and the Sophia of Jesus Christ - Parrott, Alexander (Nag Hammadi Studies, 1991)
Eugnostos and The Sophia of Jesus Christ (SJC) are two closely related tractates from the Nag Hammadi Coptic Gnostic Library and Papyrus Berolinensis 8502 (only SJC ). Here they are presented parallel with each other because they are literarily related, i.e. most of Eugnostos is also found in SJC . Eugnostos is printed in its two Coptic copies (too close to be versions), plus the fragmentary remains of a Greek copy (all with translations). This the first publication of the edited text of Eugnostos from Nag Hammadi Codex V and the first time that all these texts have been presented in one volume. Eugnostos is a non-Christian speculative cosmogony that begins with the primal invisible One, moves on to the structuring of the invisible and visible aeons and concludes at the point where the creation of this world would occur. SJC is a revelation discourse of Christ with his disciples which makes use of the bulk of Eugnostos , and adds new emphases: e.g. the special role of Christ as revealer and savior, the imprisonment of the divine element in flesh, opposition in sexual intercourse, and the commissioning of the disciples. While Eugnostos lacks essential elements of the gnostic world-view, SJC is unquestionably gnostic. If one assumes the priority of Eugnostos , these tractates provide the clearest textual evidence available of a non-gnostic and non-Christian speculative system being transformed into a system that is both gnostic and Christian. An introduction, textual notes and indices are included.